Upaya Meningkatkan Pemahaman Siswa Pada Materi Himpunan Dengan Menggunakan Pendekatan Contextual Teaching and Learning (CTL) - Ayi Suhayi Nurhidayah (Journal on Education, 2019)
The material of the set is one of the basic concepts that must be mastered by students of class VII in order to facilitate students in learning other mathematical material. The purpose of writing this PTK report is: 1) To know students' understanding of the material set in class VII A SMP Negeri 1 Cisarua, West Bandung Regency before and after using the CTL (Contextual Teaching and Learning) approach. 2) To find out the effectiveness of the effective CTL (Contextual Teaching and Learning) approach is used to improve students' understanding of the set material in class VII A SMP Negeri 1 Cisarua, West Bandung Regency. 3) To find out the differences in the results of increasing students' understanding of the material set in class VII A SMPN 1 Cisarua, West Bandung Regency before and after using the CTL (Contextual Teaching and Learning) approach